A realistic X-ray simulation for C-Arm geometry calibration - Thürauf, Sabine; Wolf, Markus; Korner, Mario; Vogt, Florian; Hornung, Oliver; Nasseri, M. Ali; Knoll, Alois (Proceedings of the IEEE RAS and EMBS International Conference on Biomedical Robotics and Biomechatronics, 2016)
Applications like cone beam computed tomographies (CBCTs) or 2D-3D overlays need a high geometrical accuracy of the C-Arm system. In order to achieve this, geometry calibrations are performed to increase the accuracy given by the kinematics of the system. Commonly X-ray images of a phantom with known geometry are taken for the calibration. The images, together with a 3D model of the phantom, serve as input for an optimizer, which estimates the pose of the C-Arm relative to the phantom. Afterwards, the estimates are used to increase the geometrical accuracy of the system.
Created from Fastlane, Scopus look-up